A new video-based tool to enhance teaching economics. (January 2018) - Kuhn, Christiane; Zlatkin-Troitschanskaia, Olga; Brückner, Sebastian; Saas, Hannes
Abstract: We present a new video-based tool developed in Germany to enhance the teaching of economics. The tool consists of authentic teacher-student interactions in economics classes to which instructors need to react. With 18 videos, the tool provides an easily accessible opportunity to assess and enhance teaching performance in economics. The tool was rated by 41 highly experienced secondary school economics teachers according to different criteria relevant for curriculum design and instructional practice, including authenticity of the simulated classroom situations, and typical difficulties and misconceptions students have in learning economics. The teachers confirm the curricular and instructional sensitivity, validity, quality and innovative approach of the tool for formative assessment and enhancement of performance in teaching economics. Based on German practical experience, the use of the tool in secondary school teacher training programs in the United States is currently being investigated.